Magnetic resonance imaging (MRI) findings in referred adult patients with headache - Hiba Khalid Salih; Dildar A. Salih (Zanco Journal of Medical Sciences)
Background and objective: Since the beginning of the medical practice, headache was considered both a therapeutic and a diagnostic challenge. According to the ranking that was made by the global burden of diseases collaborative network for causes of disabilities, headache was considered the fourth for both males and females. The aim of the study was to evaluate the findings of MRI among headache patients.